Image of the Month: How to Select the Ideal Surgical Approach in Male Anorectal Malformation with No Visible Fistula - Apte, Anisha; McKenna, Elise; Levitt, Marc A. (European Journal of Pediatric Surgery Reports, 2020)
We present a case of a 6-month-old male infant with an anorectal malformation (ARM) who underwent colostomy as a newborn, and now presents for definitive repair. A colostogram is shown to identify the malformation and to help plan for the ideal surgical approach. The case is presented with a focus on surgical strategies for management of ARM in the male infant, with questions for the readers posed in a quiz format.
Keywords: anorectal malformation; distal colostogram; anorectoplasty